Magnetic resonance images denoising using a wavelet solution to laplace equation associated with a new variational model - Upadhyay P.; Upadhyay S.K.; Shukla K.K. (My University, 2025)
In this paper by exploiting the theory of wavelet transform, a solution of Laplace equation, after changing certain initial conditions in terms of wavelet transformation is obtained. We have further applied this solution of Laplace equation to denoise magnetic resonance (MR) images from brain web dataset at different noise levels. The denoised MR images are again denoised with the help of a new proposed variational model with certain wavelet. We compared our results with the reported results of Yadav et al along with some other recently reported results. It was found that the proposed method not only outperforms the reported methods of Yadav et al but some other recently reported results also. © 2021